South Africa’s Trade Performance under Alternative Exchange Rate Regimes - Patrick, Romaine; Nyatanga, Phocenah (Journal of Economics and Behavioral Studies, 2018)
This study examined the effect exchange rates have on import and export volumes under alternative exchange rate policies adopted in South Africa over the period 1960 to 2017. Using quarterly time series data for the stated period, a log-linear error correction model is employed to estimate the country’s export and import elasticities, taking into account Gross Domestic Product (GDP), the real price of exports, the real price of imports and real exchange rates. Using the freely floating exchange rate regime as the base period, the study concluded that both export and import volumes are lower under a system of fixed exchange rates. Export and import volumes were also found to be lower under the dual exchange rate regime, relative to the freely floating exchange rate regime. In accordance with export-led growth strategies, exports were found to be higher and imports lower under a managed floating exchange rate regime. It is therefore recommended that South Africa revert to a more managed exchange rate regime, until the South African economy is developed to accommodate a freely floating exchange rate regime.